Optimization of an Operative Period at Radical Mastectomies - V. Yu. Vasilyev; Ye. M. Levite; A. M Gordova; G. R. Kaziyev (Общая реаниматология)
Blood loss volume is determined visually and approximately in most cases of surgical interventions, which most commonly leads to its underestimation, inadequate compensation, and development of hypovolemia. The latter induces peripheral vasospasm resulting in circulatory hypoxia, metabolic acidosis, diminished immunity, and worse reparative capacities of the body in the postoperative period. The transfused liquid volumes exceeding blood loss cause an increase in interstitial fluid volume, tissue edema and, hence, lead to impaired pulmonary gas exchange, enlarged postoperative wound edema, and postoperative complications. Administration of infusion media at a temperature lower than the body temperature has multiple adverse effects that impair the function of organs and systems. The typical response to hypothermia is peripheral vasospasm, followed by the development of circulatory hypoxia and metabolic acidosis. The objective of the study was to precisely estimate the volume of intraoperative blood loss and its adequate compensation and to correct central hemodynamic parameters and the body’s water sectors by nor-mothermal infusion therapy. Subjects and methods. The body’s water sectors, central hemodynamics, oxygen balance, and intraoperative blood loss volume were studied. Three groups of patients with radical mastectomy were comparatively analyzed. In Group 1 including 35 women operated on for breast cancer, the magnitude of blood loss was determined by eye and standard infusion therapy was performed, by using the mean solution temperatures of 20°C. Group 2 comprised 20 patients in whom blood loss was measured using a balance and infusion therapy was performed in accordance with the volume of the measured blood loss at the same temperature as in Group 1. Group 3 (n=18) received infusion therapy with the solutions warmed up to 37°C in accordance with blood loss volume determined applying a balance. Results. The studies have shown it necessary to monitor blood loss for its adequate compensation and to make appropriate correction of hemodynamic parameters along with normothermal infusion therapy during surgical interventions into the breast. Key words: monitoring of blood loss volume, the body’s water sectors, normothermal infusion therapy, central hemodynamics.